Transient Hyperglycemia in Hispanic Children With Acute Lymphoblastic Leukemia - Baillargeon, Jacques (2005)
BACKGROUND: Transient hyperglycemia occurs commonly during the treatment for childhood acute lymphoblastic leukemia (ALL). The purpose of this study was to examine the incidence of and risk factors for transient hyperglycemia during induction chemotherapy in Hispanic pediatric patients diagnosed with B-Precursor ALL. PROCEDURE: The study cohort consisted of 155 Hispanic pediatric patients diagnosed with ALL and treated at one of two South Texas pediatric oncology centers between 1993 and 2002. Hyperglycemia was defined as ≥2 glucose determinations of ≥200 mg/dl during the first 28 days of induction chemotherapy. RESULTS: Overall, 11.0% of the study cohort developed transient hyperglycemia during induction chemotherapy. Age and body mass index (BMI) were both positively associated with the risk of hyperglycemia. Females exhibited a substantially higher risk of hyperglycemia than males, but this association did not reach statistical significance after adjusting for other covariates. Among patients who developed hyperglycemia, 100% of those who required insulin were in the 13–18-year age group and reported a family history of diabetes. Hyperglycemic patients classified as obese (BMI ≥ 95 centile) were more than twice as likely to have required insulin therapy compared to overweight patients (BMI 85–<95 centile) and three times as likely to have required insulin compared to normal weight (BMI <85 centile) patients. CONCLUSIONS: The incidence of chemotherapy-induced transient hyperglycemia in the present study cohort is comparable to that reported in previous pediatric ALL patients. This finding is interesting in view of the elevated prevalence of obesity and the underlying dietary behaviors in this Hispanic study cohort.